Selective Subnormal IgG1 in 54 Adult Index Patients with Frequent or Severe Bacterial Respiratory Tract Infections - James C. Barton; Luigi F. Bertoli; J. Clayborn Barton; Ronald T. Acton (Journal of Immunology Research)
We characterized 54 adult index patients with reports of frequent or severe bacterial respiratory tract infections at diagnosis of selective subnormal IgG1. Mean age was 50±13 (SD) y; 87.0% were women. Associated disorders included the following: autoimmune conditions 50.0%; hypothyroidism 24.1%; atopy 38.9%; and other allergy 31.5%. In 35.5%, proportions of protective S. pneumoniae serotype-specific IgG levels did not increase after polyvalent pneumococcal polysaccharide vaccination (PPPV). Blood lymphocyte subset levels were within reference limits in most patients. Regressions on IgG1 and IgG3 revealed no significant association with age, sex, autoimmune conditions, hypothyroidism, atopy, other allergy, corticosteroid therapy, or lymphocyte subsets. Regression on IgG2 revealed significant associations with PPPV response (negative) and CD19+ lymphocytes (positive). Regression on IgG4 revealed significant positive associations with episodic corticosteroid use and IgA. Regression on IgA revealed positive associations with IgG2 and IgG4. Regression on IgM revealed negative associations with CD56+/CD16+ lymphocytes. Regressions on categories of infection revealed a negative association of urinary tract infections and IgG1. HLA-A⁎03, HLA-B⁎55 and HLA-A⁎24, HLA-B⁎35 haplotype frequencies were greater in 38 patients than 751 controls. We conclude that nonprotective S. pneumoniae IgG levels and atopy contribute to increased susceptibility to respiratory tract infections in patients with selective subnormal IgG1.